Influence of phase I periodontal therapy on levels of matrix metalloproteinase 1 and tissue inhibitor of metalloproteinase 1 - Pallavi S. Ghodpage; Rajashri A. Kolte; Abhay P. Kolte; Madhur Gupta (Saudi Dental Journal, 2014)
Background: Matrix metalloproteinase-1 (MMP-1) is a member of a family of enzymes that can degrade most extracellular matrix macromolecules. Extracellularly, MMPs are controlled by tissue inhibitors of metalloproteinases (TIMPs) and by mechanisms of pro-MMP activation. Levels of MMPs and TIMPs change during healing, inflammation, and normal tissue turnover. Herein we aimed to evaluate the levels of MMP-1 and TIMP-1 in gingival crevicular fluid (GCF) from periodontally healthy patients (control group) and chronic periodontitis patients before and after phase 1 therapy. Methods: In this study we examined 30 patients who had chronic periodontitis with probing depth sites ⩾5 mm and a clinical attachment level (CAL) ⩾5 mm. We included 30 periodontally healthy patients as a control. Clinical measurements such as plaque (PI) and gingival (GI) indices, papillary bleeding index (PBI), probing depths (PD), and CAL were recorded both before treatment (BT) and after phase I periodontal treatment (AT). Assays for MMP-1 and TIMP-1 were performed with an enzyme-linked immunosorbent assay (ELISA) method. Results: All clinical parameters were significantly reduced at the post-therapy visit. MMP-1 levels were significantly higher in patients BT than the controls; however, the patients AT were not statistically different than the controls. TIMP-1 levels in patients BT were significantly lower than in the controls and significantly lower than patients AT. We observed a significant positive correlation between GCF volume and MMP-1 levels. Furthermore, TIMP-1 levels were significantly negatively correlated with both GCF volume and all clinical parameters. Conclusions: We observed that as the extent of periodontal destruction increases, MMP-1 concentration increases and TIMP-1 concentration decreases in GCF. When chronic periodontitis patients were treated by scaling and root planing (SRP), the average MMP-1 concentrations decreased and TIMP-1 concentrations increased in GCF. Keywords: MMP-1, TIMP-1, Chronic periodontitis, Gingival crevicular fluid